2016
DOI: 10.1021/acs.jmedchem.6b00986
|View full text |Cite
|
Sign up to set email alerts
|

1,2-Benzisoselenazol-3(2H)-one Derivatives As a New Class of Bacterial Urease Inhibitors

Abstract: Urease inhibitors are considered promising compounds for the treatment of ureolytic bacterial infections, particularly infections resulting from Helicobacter pylori in the gastric tract. Herein, we present the synthesis and the inhibitory activity of novel and highly effective organoselenium compounds as inhibitors of Sporosarcina pasteurii and Helicobacter pylori ureases. These studied compounds represent a class of competitive reversible urease inhibitors. The most active compound, 2-phenyl-1,2-benzisoselena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 59 publications
4
61
0
Order By: Relevance
“…The molecular modeling studies of compound 13 binding indicated that amino groups present in the inhibitor structure form hydrogen bonds with carbonyls of Ala170 and Ala366, while the phosphinic moiety interacts with both nickel(II) ions [27]. This type of binding in the bacterial urease active site makes the aminophosphinic class of inhibitors universal, contrary to structures designed to target the thiol group of cysteines, which in some pathogenic ureases are not present at locations that are relevant to enzyme activity [40, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…The molecular modeling studies of compound 13 binding indicated that amino groups present in the inhibitor structure form hydrogen bonds with carbonyls of Ala170 and Ala366, while the phosphinic moiety interacts with both nickel(II) ions [27]. This type of binding in the bacterial urease active site makes the aminophosphinic class of inhibitors universal, contrary to structures designed to target the thiol group of cysteines, which in some pathogenic ureases are not present at locations that are relevant to enzyme activity [40, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…The tremendous efforts in this area has led to the identification of many bioactive structures [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Several enzymes, among them thioredoxin reductase [ 36 , 48 ], bacterial urease [ 49 ], and plasma membrane H+-ATPase [ 50 , 51 , 52 ], were suggested as targets for organoselenium compounds with antimicrobial properties. Furthermore, it has been reported that the antiviral effects of organoselenium compounds might be related to the inhibition of hepatitis C virus NS3 helicase [ 28 ], HIV-1 capsid dimerization [ 29 ], and nucleocapsid protein 7 [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of antimicrobial drug development, ebselen and its derivatives have been reported to: The plausible molecular mechanism behind the multiple activities of ebselen might derive from its ability to covalently Furthermore, ebselen has an inhibitory effect on H + /K + ATPase. This suggests a potential application in the treatment of H. pylori infection, as reported by Macegoniuk and co-workers [11]. Ebselen and its derivatives have also the ability to inhibit bacterial urease [11].…”
Section: 3-selenazoles and Benzoisoselenazolones Derivativesmentioning
confidence: 56%
“…This suggests a potential application in the treatment of H. pylori infection, as reported by Macegoniuk and co-workers [11]. Ebselen and its derivatives have also the ability to inhibit bacterial urease [11].…”
Section: 3-selenazoles and Benzoisoselenazolones Derivativesmentioning
confidence: 56%